La cuestión de la "solución del conflicto" entre los Estados Unidos y Cuba : precisiones, premisas, precauciones - Hernández, Rafael (Estudios Internacionales, 1994)
Opposing values and interests have always been at the root of the confrontation between the United States and Cuba. These values and interests are inserted into the more general framework of relations between the United States and Latin America. From this antagonistic alignment, questions arise regarding what are the terms of the conflict between the two countries and to what extent a certain solution to it is reasonable. This paper examines the problems that derive from world changes and that have relevance to the policy alternatives between the two countries, such as the impact of the collapse of European socialism and the end of the cold war, national insecurity, alliances and agreements, market and geopolitics, to end with the verification of a change in the North American policy towards Cuba and if perhaps this could culminate with the normalization of relations between both nations.